The Impact of Media in Cancel Culture Phenomenon - Graciela Bianca Jaafar; Herna Herna (Ikatan Sarjana Komunikasi Indonesia, 2023)
The life of our societyÂ has goneÂ through enough changes along with the development of technology. One of the changes that can be felt isÂ the appearance of digital culture such as Cancel Culture, an action where netizensÂ boycott a celebrity or a certain public figure due to his/herÂ taboo action. The purpose of this research is to know the role of the media in the cancel culture phenomenon by using Determination Technology theory. ThisÂ study usesÂ descriptive qualitative approaches withÂ Â virtual ethnography . The scope of the research l focusesÂ on the Cancellation phenomenon of theÂ Instagram accounts of @arawindak and @kite..entertainment for two reasons. The first reason is the alleged cancellation of